2006
DOI: 10.1073/pnas.0508701103
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide-binding sites revealed in the structure of plant acetohydroxyacid synthase

Abstract: The sulfonylureas and imidazolinones are potent commercial herbicide families. They are among the most popular choices for farmers worldwide, because they are nontoxic to animals and highly selective. These herbicides inhibit branched-chain amino acid biosynthesis in plants by targeting acetohydroxyacid synthase (AHAS, EC 2.2.1.6). This report describes the 3D structure of Arabidopsis thaliana AHAS in complex with five sulfonylureas (to 2.5 Å resolution) and with the imidazolinone, imazaquin (IQ; 2.8 Å). Neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
354
1
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(373 citation statements)
references
References 28 publications
10
354
1
8
Order By: Relevance
“…Entretanto, avaliando a mesma característica, Kuk et al (2003) discriminaram os biótipos S e R ao herbicida imazosulfuron da planta Bioensaios para diagnóstico da resistência aos herbicidas ... A diferente localização das mutações no gene ALS responsáveis pela resistência aos herbicidas desses cultivares pode ter causado distintos níveis de resistência, devido às mudanças da conformação da enzima ALS e à importância específica do aminoácido mutado em relação à ligação de cofatores (McCourt et al, 2006). Em sementes de Setaria viridis embebidas em diversas doses de trifluralina, foi possível diagnosticar a resistência em apenas cinco dias após a embebição nos tratamentos (Beckie et al, 1990) (Tal et al, 2000), ALS (Beckie et al, 2000) e EPSPs (Escorial et al, 2001;Perez & Kogan, 2003).…”
Section: Resultsunclassified
“…Entretanto, avaliando a mesma característica, Kuk et al (2003) discriminaram os biótipos S e R ao herbicida imazosulfuron da planta Bioensaios para diagnóstico da resistência aos herbicidas ... A diferente localização das mutações no gene ALS responsáveis pela resistência aos herbicidas desses cultivares pode ter causado distintos níveis de resistência, devido às mudanças da conformação da enzima ALS e à importância específica do aminoácido mutado em relação à ligação de cofatores (McCourt et al, 2006). Em sementes de Setaria viridis embebidas em diversas doses de trifluralina, foi possível diagnosticar a resistência em apenas cinco dias após a embebição nos tratamentos (Beckie et al, 1990) (Tal et al, 2000), ALS (Beckie et al, 2000) e EPSPs (Escorial et al, 2001;Perez & Kogan, 2003).…”
Section: Resultsunclassified
“…To determine the prevalence of AHAS isozymes across a sample of clinically relevant bacteria, we performed a phylogenetic analysis on the AHAS catalytic subunit, which contains the SH binding site (2,16). As seen previously (13,22,23), type I AHAS was exclusively present in Enterobacteriaceae (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial isozymes of AHAS are composed of a catalytic and a regulatory subunit that are encoded by adjacent genes. Catalytic subunits of AHAS were identified by searching the genomes of select organisms using the Enzyme Commission number 2.2.1.6 (2,16). In most genomes, multiple genes have been annotated as AHAS catalytic subunits.…”
Section: Methodsmentioning
confidence: 99%
“…Structural data describing the ALS protein in complex with ALS-inhibiting herbicides have been reported (McCourt et al, 2006). It has also been shown that it is difficult to predict substrate preferences from primary sequences in CYP72A proteins (Nelson and WerckReichhart, 2011).…”
Section: Application Of Cyp72a31 and Cyp81a6 Genes In Weed Managementmentioning
confidence: 99%